First record of Least Sandpiper Calidris minutilla for Buenos Aires province and review of its status in Argentina - Martínez Curci, Natalia Soledad; Pretelli, Matías Guillermo; Cavalli, Matilde; Isacch, Juan Pablo; Loredo, M. Ángeles (Wader Study)
The Least Sandpiper Calidris minutillais a Nearctic migrant shorebird that breeds in the North American taiga and subarctic tundra biomes and mainly spends the nonbreeding season in the southern United States, Central America, the Caribbean, and northern South America. There are only two extralimital records of this species for Argentina with photographic evidence: one came from La Pampa province and other from Córdoba province.We observed a single Least Sandpiperin the banks of Arroyo Chico (37 o 26´8"S, 57o 11´43.49"W), a small stream that crosses Medaland Ranch. A White-rumped Sandpiper Calidris fuscicollis accompanied the Least. Approximately 50 meters from them, also on the banks of Arroyo Chico, there was a mixed flock of resting shorebirds comprising 63 Hudsonian Godwits Limosa haemastica, 11 American Golden Plovers,six Black-necked Stilts Himantopus mexicanus, two Stilt Sandpipers Calidris himantopus, two White-rumped Sandpipers, and two Lesser Yellowlegs Tringa flavipes; there were also three Neotropic Cormorants Phalacrocorax brasilianus. The Least Sandpiper was feeding by probing in the mud, but quickly flew as we approached to take a photograph. It was easily identified by its smaller size compared to the White-rumped and by its yellowishgreen short legs with longish toes. Fil: Martínez Curci, Natalia Soledad. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Pretelli, Matías Guillermo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Cavalli, Matilde. Consejo Nacional de ...